Verification of the mixed layer depth in the OceanMAPS operational forecast model for Austral autumn ... : التحقق من عمق الطبقة المختلطة في نموذج التنبؤ التشغيلي لـ OceanMAPS لخريف أستراليا ... - Daniel Boettger; Robin Robertson; Gary B. Brassington (OpenAlex, 2018)
Abstract. The ocean mixed layer depth is an important parameter describing the exchange of fluxes between the atmosphere and ocean. In ocean modelling a key factor in the accurate representation of the mixed layer is the parameterization of vertical mixing. An ideal opportunity to investigate the impact of different mixing schemes was provided when the Australian Bureau of Meteorology upgraded its operational ocean forecasting model, OceanMAPS to version 3.0. In terms of the mixed layer, the main difference between the old and new model versions was a change of vertical mixing scheme from that of Chen et al. (1994) to the General Ocean Turbulence Model. The model estimates of the mixed layer depth were compared with those derived from Argo observations. Both versions of the model exhibited a deep bias in tropical latitudes and a shallow bias in the Southern Ocean, consistent with previous studies. The bias, however, was greatly reduced in version 3.0, and variance between model runs decreased. Additionally, ... : الملخص: يعد عمق الطبقة المختلطة للمحيطات معلمة مهمة تصف تبادل التدفقات بين الغلاف الجوي والمحيطات. في نمذجة المحيطات، يتمثل العامل الرئيسي في التمثيل الدقيق للطبقة المختلطة في تحديد معلمات الخلط الرأسي. تم توفير فرصة مثالية للتحقيق في تأثير مخططات الخلط المختلفة عندما قام المكتب الأسترالي للأرصاد الجوية بتحديث نموذج التنبؤ التشغيلي بالمحيطات، OceanMAPS إلى الإصدار 3.0. من حيث الطبقة المختلطة، كان الاختلاف الرئيسي بين إصدارات النموذج القديم والجديد هو تغيير مخطط الخلط الرأسي من مخطط Chen et al. (1994) إلى نموذج اضطراب المحيط العام. تمت مقارنة تقديرات النموذج لعمق الطبقة المختلطة مع تلك المستمدة من ملاحظات Argo. أظهرت كلتا النسختين من النموذج تحيزًا عميقًا في خطوط العرض الاستوائية وتحيزًا ضحلًا في المحيط الجنوبي، بما يتفق مع الدراسات السابقة. ومع ذلك، انخفض التحيز بشكل كبير في الإصدار 3.0، وانخفض التباين بين عمليات تشغيل النموذج. بالإضافة إلى ذلك، تحسنت مهارة النموذج ضد علم المناخ بشكل كبير. استبعد المزيد من التحليل التغييرات في دقة النموذج خارج المنطقة الأسترالية التي لها تأثير كبير على هذه النتائج، تاركة ...